Beyond survival: how well do transplanted livers work? A preliminary comparison of standard‐risk, high‐risk, and living donor recipients. (27th April 2014) - Miller‐Matero, Lisa R.; Eshelman, Anne; Paulson, Daniel; Armstrong, Rachel; Brown, Kimberly A.; Moonka, Dilip; Abouljoud, Marwan
Abstract To help decrease mortality on the liver transplant waitlist, transplant centers are using living donors (LD) and high‐risk donors (HRD) in addition to standard‐risk donors (SRD). HRD is defined as having a donor risk index score higher than 1.6, which suggests a great risk of graft failure. Recent studies have examined survival rates between HRD and SRD recipients; however, little is known about outcomes other than survival, specifically psychosocial outcomes. The purpose of this preliminary, prospective study was to compare post‐transplant psychosocial and recovery outcomes between SRD and LD and HRD liver recipients. These outcomes include cognitive functioning, psychological distress, quality of life, and self‐reported and objective measures of recovery. Eighty‐four patients provided baseline and six‐month post‐transplant data. There were generally no statistically significant differences at baseline or the six‐month follow‐up, suggesting that patients receiving HRD livers have similar outcomes to those who receive SRD livers. However, some effect sizes suggest potential advantages for LD recipients compared to SRD recipients. Transplant centers may be more willing to encourage patients to accept HRD or LD livers knowing that they may have comparable outcomes to SRD recipients, which also has implications for the transplant waitlist.